Development and Validation of the Dissociative Symptoms Scale. (January 2018) - Carlson, Eve B.; Waelde, Lynn C.; Palmieri, Patrick A.; Macia, Kathryn S.; Smith, Steven R.; McDade-Montez, Elizabeth
The Dissociative Symptoms Scale (DSS) was developed to assess moderately severe levels of depersonalization, derealization, gaps in awareness or memory, and dissociative reexperiencing that would be relevant to a wide range of clinical populations. Structural analyses of data from four clinical and five nonclinical samples ( N = 1, 600) yielded four factors that reflected the domains of interest and showed good fit with the data. Sample scores were consistent with expectations and showed very good internal consistency and temporal stability. Analyses showed consistent evidence of convergent and divergent validity, and posttrauma elevations in scores and in patients with posttraumatic stress disorder provided additional evidence of construct validity. Item response theory analyses indicated that the items assessed moderately severe dissociative experiences. Overall, the results provide support for the reliability and validity of DSS total and subscale scores in the populations studied. Further work is needed to evaluate the performance of the DSS relative to structured interview measures and in samples of patients with other psychological disorders.